Response of shear-deficient reinforced circular RC columns under lateral impact loading - Demartino, C.; Wu, J.G.; Xiao, Y. (International journal of impact engineering, 2017)
This paper reports the results of an extensive experimental investigation on the behavior of shear-deficient reinforced circular RC columns under lateral impact loading. First, it provides a brief literature review on studies of the dynamic response induced by vehicle collisions on RC columns highlighting the lack of experimental tests on vertical elements. In this context, a novel facility for testing of vertical elements under lateral impact loading was realized. Two different types of RC columns characterized by different hoop spacing were tested, representing a one-third scaled model of a reinforced circular bridge pier, designed with obsolete design practice with particular reference to non-seismic areas. A total of 10 specimens (5 for each type) were tested under a lateral rigid-hammer impact at different impact velocities (2.25, 3 and 4.5 m/s) and boundary conditions (cantilever and fixed-simply-supported). The impact load was applied at the typical vehicular impact location, i.e. near the base. A description of the impact and reaction forces, of the lateral displacements and accelerations, of the damage development and of the post-impact damage is given. The dynamic response and the observed damage are found to be significantly affected by the column type, the impact velocity and the boundary condition. A brittle shear-type damage was observed, characterized by one main diagonal crack originating from the base of the column to the impact point, revealing the high vulnerability of these structural elements.